2018
DOI: 10.14196/mjiri.32.101
|View full text |Cite
|
Sign up to set email alerts
|

Application of the short form of quality of life instrument version 2 in a large population of Tehran

Abstract: Background: Quality of life (QoL) is now considered as a key indicator in health studies. Therefore, this study was conducted to evaluate QoL in the general population of Tehran (capital of Iran) using SF-12v2 questionnaire and determine some factors associated with it. Methods: This was part of a large population-based cross sectional study conducted in Tehran, Iran, in 2011. Participants were selected from all districts of Tehran using multistage cluster random sampling met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
2
1
0
Order By: Relevance
“…On the other hand, a significant association between sex and HRQOL was limited to the health domains of BP and GH. This finding is consistent with previous studies that also agreed that being female was associated with poor BP and GH [ 41 ]. Working females invested more energy and faced high strain in order to cope with noticeable demanding roles, namely, responsibilities within the home and managing tasks at the workplace [ 42 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…On the other hand, a significant association between sex and HRQOL was limited to the health domains of BP and GH. This finding is consistent with previous studies that also agreed that being female was associated with poor BP and GH [ 41 ]. Working females invested more energy and faced high strain in order to cope with noticeable demanding roles, namely, responsibilities within the home and managing tasks at the workplace [ 42 ].…”
Section: Discussionsupporting
confidence: 94%
“…Therefore, these situations eventually affect certain joys of life, particularly physical, psychological, and social well-being. Moreover, the findings in this study are in line with past studies that mention that a family history of chronic disease is significantly associated with poor mental health [ 41 ]. Family history has been a known risk factor of developing several chronic diseases since it reflects inherited genetic susceptibility as well as shared behaviour and environment among family members [ 47 ].…”
Section: Discussionsupporting
confidence: 92%
“…A study showed that treatment of chemo-radiotherapy induced oral mucositis due to lung and head, and neck cancer possess over 17,000$ (USD) incremental cost per patient [ 7 ]. So for the evaluation outcome of patients with oral mucositis to reflect the full impact of oral condition, assessment of the quality of life as a critical health-related indicator, besides the biomedical parameters is necessary [ 8 , 9 ]. The definition of quality of life, according to the World Health Organization is “an individual’s perception of their position in life in the context of the culture, and value systems in which they live, and in relation to their goals, expectations, standards, and concerns” [ 10 ].…”
Section: Introductionmentioning
confidence: 99%